Factors Affecting Intention of Consumers in Using Face Recognition Payment in Offline Markets: An Acceptance Model for Future Payment Service - Nan, Dongyan; Kim, Yerin; Huang, Jintao; Jung, Hae Sun; Kim, Jang Hyun (Frontiers in Psychology, 2022)
Face recognition payment, an innovative financial technology service, is a recently developed mode of payment service that has garnered attention in the offline market, particularly in China. However, studies examining the adoption of face recognition payment by consumers are scarce. Therefore, this study proposed a causal model built on Unified Theory of Acceptance and Use of Technology and key predictors related to the intention of using face recognition payment were identified. The structural equation model-based results obtained from 305 Chinese participants demonstrated that the intention was most affected by relative advantage. In addition, performance expectancy, effort expectancy, social influence, and perceived risk had significant impact as well. However, trust was found to not significantly affect consumers’ intentions, despite it negatively influencing perceived risk. Thus, the results of this study are expected to provide a set of guidelines for companies regarding the implementation of face recognition payment.